2013
DOI: 10.1371/journal.pone.0066396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Analysis of Schistosoma japonicum Plasma Membrane Repair Relative Gene Myoferlin

Abstract: Myoferlin is a member of the ferlin family of proteins, which are involved in plasma membrane repair, and has been identified as one of the tegument proteins of Schistosoma japonicum. The tegument proteins are potential candidates for vaccines and new drug targets. In this study, myoferlin of S. japonicum (SjMF) was cloned, expressed and characterized, the potential of SjMF recombinant protein (rSjMF) as a vaccine candidate was evaluated, and the effect of praziquantel on SjMF was detected by Real-time PCR. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The same antigen formulated with FCA or ISA 206 induced a moderate mixed Th1/Th2 immune response post vaccination, but this mixed immune response shifted to a Th2 response after parasite maturation and the onset of egg production [ 45 ]. This mixed immune response was also observed by Lin et al , who used ISA 206 as an adjuvant for the SjMF antigen in a murine model [ 23 ]. This study found reduced worm burdens (21.8%–23.2%) and liver egg number (42.5%–28.3%) [ 23 ].…”
Section: Major Schistosome Vaccine Adjuvants Under Preclinical Andsupporting
confidence: 73%
See 1 more Smart Citation
“…The same antigen formulated with FCA or ISA 206 induced a moderate mixed Th1/Th2 immune response post vaccination, but this mixed immune response shifted to a Th2 response after parasite maturation and the onset of egg production [ 45 ]. This mixed immune response was also observed by Lin et al , who used ISA 206 as an adjuvant for the SjMF antigen in a murine model [ 23 ]. This study found reduced worm burdens (21.8%–23.2%) and liver egg number (42.5%–28.3%) [ 23 ].…”
Section: Major Schistosome Vaccine Adjuvants Under Preclinical Andsupporting
confidence: 73%
“…This mixed immune response was also observed by Lin et al , who used ISA 206 as an adjuvant for the SjMF antigen in a murine model [ 23 ]. This study found reduced worm burdens (21.8%–23.2%) and liver egg number (42.5%–28.3%) [ 23 ]. Notably, the novel adjuvant ISA 70M provided an enhanced humoral and cell-mediated immune response in this study; it comprises a high grade injectable mineral oil and an extremely refined emulsifier obtained from mannitol and purified oleic acid of vegetable origin, and is a modified version of the successful veterinary adjuvant, ISA 70.…”
Section: Major Schistosome Vaccine Adjuvants Under Preclinical Andsupporting
confidence: 73%
“…Our previous observation revealed that when schistosomes were treated with a complete dose (200 mg/kg) of PZQ, the tegument and sub-tegument of the worms were severely damaged, which finally resulted in the deaths of the treated worms. However, when the worms were treated with an incomplete dose (40 mg/kg) of PZQ, the damaged tegument recovered gradually post-treatment [ 44 ]. In this study, we noticed the similar result.…”
Section: Discussionmentioning
confidence: 99%
“…Two weeks after the final vaccination, mice were challenged percutaneously with 40 ± 1 viable cercariae, as described by Smithers and Terry [ 14 , 29 ]. Six weeks after challenge, worms were perfused from the hepatic portal system and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Schistosomes must evade the host immune responses, which is attributed in part to their tegument [ 11 ]. Thus, schistosomal proteins on the surface of the tegument and some regulatory proteins that impede the complement cascade might represent ideal molecules for the discovery of vaccine candidates [ 9 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%